PROJECT-BASED LEARNING WITH DIFFERENTIATED STRATEGIES IN GROWING METACOGNITION SKILLS OF JUNIOR HIGH SCHOOL LEARNERS - silaban, bajongga; Br Surbakti, Mariana; Simbolon, Lamtiur Verawati; Lase, Leni Marlina (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2023)
This research aims to determine learners metacognitive skills after participating in project-based learning with differentiated strategies on vibration and wave material. This research was carried out in the even semester of the 2022/2023 academic year of 8th grade learners state junior high school 7 Medan. The type of research was a pre-experiment in the form of a one-group pre-test post-test design. The population was all 8th of 9 classes, and a sample 8th-2 was 33 learners withdrawal was carried out by purposive sampling. Pilot was carried out in class 8th of state junior high school 21 Medan as many as 14 people with the result that the problems were valid and reliable with a high level of difficulty according to metacognitive needs.The average activity of learners in the auditory, kinesthetic and visual learning style groups is quite good with a score of 24.08 respectively; 23.58; and 31.05. Meanwhile, the total average pretest and posttest metacognitive skills were 32.24 (undevelop) and 72.96 (starting to develop), respectively. The paired differences t-test with the SPSS 26 application was used to test the hypothesis and obtained a value tcount = -15.173 with a sig value. 0.000, which concludes that the hypothesis is accepted, namely that differentiation strategies influence the metacognitive skills of junior high school students. The <N-Gain> test index value was obtained at 59.45%, which indicates the percentage of effectiveness of project-based learning in growing learners metacognitive skills. KeyWords: Project-based learning; differentiated strategies; metacognition skills